Efektivitas Latihan Jalan terhadap Penurunan Kolesterol pada Individu Risiko Stroke di Kampung Cibulan Tangerang - Hayah, Zahratul; Puput Dinda Kurniawan, Ganesa; Laela Abida, Liza (Jurnal Terapi Wicara dan Bahasa, 2025)
Background: Hypercholesterolemia is a major risk factor for stroke, contributing to atherosclerosis and narrowing of blood vessels. Physical activity, such as walking exercise, can enhance fat metabolism and improve lipid profiles, thereby reducing cholesterol levels. Walking is an inexpensive, accessible, and effective physiotherapy intervention for improving cardiovascular health. Objectives: To examine the effectiveness of walking exercise in reducing cholesterol levels in individuals at risk of stroke in Kampung Cibulan, Tangerang. Methods: This study applied a pre-experimental design with a one-group pretest-posttest approach. A total of 10 participants were selected through purposive sampling. The intervention consisted of walking exercise three times per week for eight weeks. Cholesterol levels were measured before and after the intervention using Point of Care Testing (POCT). Results: The average cholesterol level decreased from 256,1 mg/dL before the intervention to 237,0 mg/dL after. The Paired Sample T-Test revealed a significance value of 0.000 (p < 0.05), indicating a significant difference before and after the intervention. Conclusion: Walking exercise significantly reduces cholesterol levels in individuals at risk of stroke and can serve as a non-pharmacological strategy for stroke prevention. Keywords : Cholesterol, Stroke Risk, Walking Exercise